2010
DOI: 10.1128/jvi.00727-09
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Choriomeningitis Virus-Induced Mortality in Mice Is Triggered by Edema and Brain Herniation

Abstract: Although much is known about lymphocytic choriomeningitis virus (LCMV) infection and the subsequent immune response in its natural murine host, some crucial aspects of LCMV-mediated pathogenesis remain undefined, including the underlying basis of the characteristic central nervous system disease that occurs following intracerebral (i.c.) challenge. We show that the classic seizures and paresis that occur following i.c. infection of adult, immunocompetent mice with LCMV are accompanied by anatomical and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Bars, 50 µm. pupils in humans and mice (Matullo et al, 2010). However, pupillary reactivity was normal in Nemo beKO mice (Fig.…”
mentioning
confidence: 85%
“…Bars, 50 µm. pupils in humans and mice (Matullo et al, 2010). However, pupillary reactivity was normal in Nemo beKO mice (Fig.…”
mentioning
confidence: 85%
“…After development of the in situ hybridization signal using a standard procedure (35), the sections were rinsed in Tris-buffered saline (TBS) buffer containing 1% Triton and then incubated with monoclonal Alexa 488-conjugated mouse anti-glial fibrillary acidic protein (GFAP) IgG1 (5 g/ml; A21294; Invitrogen, Denmark), Alexa 488-conjugated mouse IgG1 isotype control (5 g/ml; MG120; Caltag Laboratories), monoclonal rat anti-CD3 (2.5 g/ml; MCA500A488; Serotec, Germany) plus Alexa 594-conjugated donkey-anti-rat IgG (10 g/ml; A21209; Invitrogen), or rat IgG2a isotype control (2.5 g/ml; 26D11204; Nordic BioSite ApS, Denmark) plus Alexa 594-conjugated donkey-anti-rat IgG (10 g/ml) diluted in TBS buffer plus 10% bovine serum. After a final rinse in TBS, sections were counterstained with DAPI (4=,6-diamidino-2-phenylindole) nuclear staining.…”
Section: Isolation Of Total Rna For Quantitative Pcr (Q-pcr)mentioning
confidence: 99%
“…Upon contact between incoming CD8 T cells and virus-infected cells in different parts of the CNS, large amounts of type II IFN are released, further increasing the local production of important chemoattractants, including CXCL10 (8). The whole process culminates in a severe CD8 ϩ T-cell-mediated inflammatory reaction in essential parts of the CNS, cerebral edema, and death 7 to 9 days after virus inoculation (8,35). Using IFNARdeficient (IFNAR Ϫ/Ϫ ) mice, we have previously shown that type I IFNs are essential in activating certain aspects of the local antiviral host response, including the early production of CXCL10 (8).…”
mentioning
confidence: 99%
“…This can give rise to a dangerous condition wherein fluid accumulates to an intolerable level within the confines of the skull resulting in herniation and death. Evidence for this mode of fatality is supported by a recent study that used MRI to demonstrate that edema was only detected in the brains of LCMV-infected mice at the terminal stage of disease (Matullo et al 2009). This study further demonstrated that death was associated with unilateral papillary dilation (indicative of uncal herniation) and breakdown of the ventricular system.…”
Section: Lymphocytic Choriomeningitis Virusmentioning
confidence: 96%
“…This explains the profound breakdown of the blood-CSF barriers. However, several groups have reported that the BBB is also disrupted during LCMV-induced meningitis (Kim et al 2009; Marker et al 1984; Matullo et al 2009), and it is known that breakdown of the BBB alone can result in seizures (Marchi et al 2007). Therefore, while BBB breakdown might not be the sole factor responsible for fatalities in this model (Matullo et al 2009), this event likely contributes to neurological complications such as seizures and might in fact enhance the probability of a fatal outcome.…”
Section: Lymphocytic Choriomeningitis Virusmentioning
confidence: 99%